Trust formation in digital sharia gold pawn services: The interplay of sharia compliance, risk perception, and financial literacy among young consumers - Ririn Riani; Sahril Fauzi (The Journal of Religion and Communication Studies, 2026)
Background: The rapid digitalization of Islamic financial services has transformed gold pawn transactions, particularly among young consumers, whose adoption decisions are influenced by Sharia compliance, financial literacy, digital service quality, perceived risk, and trust. However, empirical evidence integrating these factors into a unified behavioral framework remains limited. Methods: This study employed a quantitative cross-sectional design involving 171 Millennials and Generation Z respondents in the Greater Jakarta Area (Jabodetabek), Indonesia. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. Findings: The results indicate that Sharia compliance, financial literacy, and digital service quality positively influence trust, whereas perceived risk negatively affects trust. Trust emerges as the strongest predictor of intention to use digital Sharia gold pawn services, confirming its central mediating role in translating ethical, technological, and cognitive factors into behavioral intention. The proposed model demonstrates substantial explanatory and predictive capability. Conclusion: Trust is the primary mechanism linking Sharia compliance, financial literacy, digital service quality, and perceived risk with young consumers' intention to use digital Sharia gold pawn services. Strengthening ethical governance, enhancing financial literacy, improving digital service quality, and mitigating perceived risk are therefore essential to increase adoption of digital Islamic financial services. Novelty/Originality of this article: This study develops an integrated trust-based framework by combining the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) with Sharia compliance, financial literacy, digital service quality, and perceived risk to explain young consumers' intention to use digital Sharia gold pawn services in Indonesia.